Diagnostic and prognostic significance of neurofilament light chain NF-L, but not progranulin and S100B, in the course of amyotrophic lateral sclerosis: Data from the German MND-net. Issue 1 (2nd January 2017) - Steinacker, Petra; Huss, André; Mayer, Benjamin; Grehl, Torsten; Grosskreutz, Julian; Borck, Guntram; Kuhle, Jens; Lulé, Dorothée; Meyer, Thomas; Oeckl, Patrick; Petri, Susanne; Weishaupt, Jochen; et al.
Abstract: There is a need for diagnostic, prognostic, and monitoring blood biomarkers for ALS. We aimed to analyse and compare proposed candidate markers for disease progression in the course of ALS. Blood samples were taken from 125 ALS patients, including nine patients with C9orf72 or SOD1 mutation, at regular intervals of six months. ALS patients were characterized by the ALS functional rating scale (ALSFRS-R) and the Edinburgh Cognitive and Behavioural ALS Screen (ECAS). We quantified neurofilament light chain (NF-L), S100B, and progranulin (PGRN) and analysed it in relation to disease progression. Results showed that, at baseline, serum concentrations of NF-L but not PGRN or S100B discriminated significantly between ALS and controls. Within 24 months follow-up the marker concentrations remained stable. Baseline serum NF-L levels correlated with survival time, which was confirmed in subgroups with fast, intermediate, and slow disease progression and there was a weak association with disease duration. For S100B and PGRN we found an association with ALSFRS-R score changes and a trend for decreased levels in the fast progressor subgroup. In conclusion, serum NF-L in any ALS disease stage is a promising marker to support diagnosis and predict outcome, while serum PGRN and S100B are only of minor prognostic value.